Preservation over time of dried acellular esophageal matrix. (22nd October 2018) - Giobbe, Giovanni G; Zambon, Alessandro; Vetralla, Massimo; Urbani, Luca; Deguchi, Koichi; Pantano, Maria F; Pugno, Nicola M; Elvassore, Nicola; De Coppi, Paolo; Spilimbergo, Sara
Abstract: Preservation of acellular matrices represents a big challenge for the improvement of tissue engineering. In this work, a new method to preserve over time a decellularized esophageal scaffolds was explored. Dried and sterile acellular esophagi were obtained with a combined treatment of ethanol and a subsequent supercritical CO2 drying. Preservation of the extracellular matrix architecture, collagen content, and mechanical properties up to 6 months demonstrated the efficiency of the methodology with implications in natural scaffold storage. In vitro support of mesenchymal stem cells showed a promising indication to the further use of the technology in pre-clinical and clinical application.